Fishing and fecundity: The impact of exploitation on the reproductive potential of a deep-water fish, orange roughy (Hoplostethus atlanticus) - Pitman, L.; Haddy, J.; Kloser, Rudy (Elsevier BV, 2013)
To assess the impact of exploitation on the fecundity and reproductive potential of orange roughy, historic biological data from when exploitation began (1987-1992) is compared with a current day assessment (2010) of the eastern Tasmanian stock. Findings highlight that fecundity was negatively related to stock size (r2=0.95, F=80.11, P<0.05), with length standardised fecundity increasing from 41,145±1363 in 1992 to 59,236±1047 eggs in 2010. This density dependent increase suggests that from the onset of the fishery (1987) length standardised fecundity has increased by 73%. Modelling this increase based on the 2006 stock assessment showed that the female spawning stock biomass was at 19% of virgin levels, whereas the total reproductive potential was markedly higher and estimated to be at 32% of virgin levels. The biological mechanisms of this compensatory effect were also investigated and showed fecundity was not related to ovarian atresia levels but was positively related to body condition, liver condition and ovarian lipid levels. The implications of these findings for stock recovery and management are discussed and suggest that the stock is in a better position to recover from overexploitation than would be expected if only spawning stock biomass were considered. © 2013 Elsevier B.V.